Free Vibrations of Thin-Walled Box-Section Bars Allowing for Shear Strains - Gavrilov, Aleksandr; Grebenyuk, Grigoriy; Morozov, Nikolay; Grehov, Andrey (International Journal of Engineering and Technology, 2018)
Purpose. The purpose is to study free vibrations of thin-walled bar with combined bisymmetrical section allowing for the effects of shear strains.Methods. We used the main hypothesis of V.Z.Â Vlasov concerning thin-walled bars. Solving motion equations analytically, we used the method of initial parameters and the known methods for differential equations solution. In the natural experiment we applied Autodesk Inventor system. In the course of the natural experiment on shaker, we used the method of smooth change in the frequency of sinusoidal vibrations.Results. We provide the analytical solutions of the shapes and the natural frequencies of thin-walled bar with combined bisymmetrical section allowing for shears caused by bends and constrained torsion. We compared the results of the calculations conducted in CAE system and the results of the full-scale experiment to determine the frequencies of vibrations of box beam.Conclusions. The results showed that the analytical calculations are in good compliance with the results of numerical and physical experiments and can be used for dynamic calculations of thin-walled structural elements, in particular, for the prevention of the destruction of structures in the event of resonance phenomena.Â Â